Isolasi dan Uji Antibakteri Minyak Daun Sirih Hijau dan Merah Terhadap Streptococcus mutans. - Rizkita, Aden Dhana; Cahyono, Edy; Mursiti, Sri (Indonesian Journal of Chemical Science, 2017)
The purpose of this research is to identify the chemical content and compare the antibacterial effect of Piper betle L and Piper crocatum R oil against Streptococcus mutan. Betel oil is made at 100%, 75%, 50%, 25% concentration and amoxicillin 0.2% as positive control and propylene glycol as negative control. The research method started with oil isolation using distillation of steam and water then identified the content using GC-MS. Antibacterial activity was tested against Streptococcus mutans by disc diffusion method. The results of this research indicate that Piper betle L and Piper crocatum R oil contains terpenoid group compounds. After being characterized using GC-MS, betel oil contains 5 major active compounds that have antibacterial activity that is Sabinene, Myrsene, Camphene, Germacrene and Î² - Chariophillene. Piper betle oil has better antibacterial properties than Piper crocatum oil with clear zone reaches 10.5 mm while Piper crocatum oil is 7.1 mm.